The oldest representative of sciarid genus Leptosciarella (Diptera) from the lowermost Eocene amber of Oise (France) - Hebert, Florence; Muller, Valerie Ngo; Nel, Andre (Zootaxa, 2025)
The sciarid Leptosciarella (Leptosciarella) menzeli sp. nov. is described from the lowermost Eocene amber of Oise (France). ‘Sciara’ jucheti Camier & Nel, 2019, from the same amber, is ‘placed here into the genus Leptosciarella Tuomikoski and within this, in the subgenus Leptosciarella sensu stricto. Both represent the oldest known records of the genus Leptosciarella, previously recorded from the middle Eocene Baltic amber. These two fossils show that the Sciaridae were already well diversified during the lowermost Eocene, suggesting that these sciarid flies appeared during the Cretaceous, even if the current Mesozoic record of this family is uncertain.